Microabrasión dental para pacientes odontopediátricos: Una alternativa estética - Álvarez Páucar, María (2009)
The dental microabrasion treatment is an effective and conservative procedure against enamel surface defects. The white spots appear frequently in children because inactive enamel caries, hypoplasia and fluorosis. When these spots affect anterior teeth produce an aesthetic effect. We describe two cases of enamel microabrasion of the upper incisors for both cases using 37 % H3PO4 and a mechanical technique (micromotor) in a 7 year old child with enamel hypoplasia and a 7 year old boy with inactive enamel caries. The aim of study was to compare affectivity of enamel microabrasion with 37% H3PO4 and pumice using different gadgets for this mechanical technique. After the first microabrasion session, the best result was the one using resin polishing burs and home made acrylic pads respect to the group which use rubber points, but these differences did not longer appeared in the afterward sessions.